2017
DOI: 10.1177/1747954117710513
|View full text |Cite
|
Sign up to set email alerts
|

Laterality frequency, team familiarity, and game experience affect kicking-foot identification in Australian football players

Abstract: This study examined whether laterality frequency, team familiarity, and game experience affected preferred kicking foot identification in professional Australian Football players. Using a repeated-measures experimental design, 13 and 10 players, respectively, identified the kicking foot of 30 teammates and 30 opponents using static images in a randomised sequence. Accuracy (%), reaction time (RT ms), and discrimination capability indices were examined. Overall, participants were less accurate and had slower re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The finding that high performance Gaelic football players predominantly relied on their dominant side for most skill executions is consistent with previous research on male athletes in other sports ( Carey et al, 2001 , 2009 ; Moore et al, 2017 ; Stöckel & Vater, 2014 ; Stöckel & Weigelt, 2012 ). Differences between skills were generally small, consistent with Carey et al’s (2001) analysis of various soccer skills executed during open play (i.e., not set piece skills).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The finding that high performance Gaelic football players predominantly relied on their dominant side for most skill executions is consistent with previous research on male athletes in other sports ( Carey et al, 2001 , 2009 ; Moore et al, 2017 ; Stöckel & Vater, 2014 ; Stöckel & Weigelt, 2012 ). Differences between skills were generally small, consistent with Carey et al’s (2001) analysis of various soccer skills executed during open play (i.e., not set piece skills).…”
Section: Discussionsupporting
confidence: 91%
“…Given a well-established bias towards using the dominant hand or foot ( Carey et al, 2001 , 2009 ; Moore et al, 2017 ; Stöckel & Vater, 2014 ; Stöckel & Weigelt. 2012 ), we would expect players to act against that bias when circumstances dictate (i.e., when an opponent is preventing the preferred use of the dominant side, when proximity to the pitch boundaries encourage use of a particular side, or when chances of success are increased by using the non-dominant side; Stöckel & Vater, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Avgerinos and Gokpinar (2016) found that team familiarity leads to enhanced productivity when teams are performing complex tasks (Espinosa et al, 2007;Huckman et al, 2009). Moreover, professional competitive sporting teams also perform within specific routines and standardized processes, and studies such as Moore et al (2017) show how high familiarity leads to greater success in competitive teamwork, such as kicking accuracy and reaction time of professional football players. Sieweke and Zhao (2015), who use basketball teams in their research, report that there is an inverted Ushaped relationship between team familiarity and team coordination efforts, but the leader's team-specific experience moderates this relationship.…”
Section: Context and Work Environmentmentioning
confidence: 99%